Marcelo Diamand's contributions to economic theory: through the lenses of the classical-keynesian approach. A formal representation of unbalanced productive structures - Dvoskin, Ariel (2015)
We examine both conceptually and in formal terms the contributions by the structuralist economist Marcelo Diamand, which all turn round the notion of unbalanced productive structure, and its implications on income distribution, the general price level and output dynamics in Latin American countries, with special focus on Argentina. We argue that Diamand´s work provides a very useful framework to understand why institutionally-historically-determined real wage and real exchange rates may, on the one hand, explain the relatively low productivity of the industrial sector and, on the other hand, cause devaluations to be both inflationary and contractionary, as it has been the case in many Latin American countries that attempted to initiate an industrialization process by import substitution.